Biochemical study of the effects of cilostazol in rats subjected to acute ischemia and reperfusion of hind limbs - Souza Júnior,Sylvio Sebastião de (2013)
PURPOSE: To investigate whether cilostazol has a protective effect on acute ischemia and reperfusion of hind limbs of rats through study of biochemical variables in blood and urine. METHODS: Forty six animals were randomized and divided into two groups. Group I received a solution of cilostazol (10 mg/Kg) and group II received saline solution 0.9% (SS) by orogastric tube after ligature of the abdominal aorta. After four hours of ischemia the animals were divided into four subgroups: group IA (Cilostazol): two hours of reperfusion. Group IIA (SS): two hours of reperfusion. Group IB (Cilostazol): six hours of reperfusion. Group IIB (SS) six hours of reperfusion. After the reperfusion period, was held to collect urine and blood for biochemical measurements. The biochemical parameters studied were: urea, creatinine, sodium, potassium and myoglobin in blood and urea, creatinine, myoglobin in urine. RESULTS: There was no statistically significant difference between groups. CONCLUSION: Cilostazol had no protective effect on ischemic acute reperfusion of hind limbs of rats in this model.